Review of machine perfusion studies in vascularized composite allotransplant preservation - Duru, Çağdaş; Biniazan, Felor; Hadzimustafic, Nina; D'Elia, Andrew; Shamoun, Valentina; Haykal, Siba (Frontiers in Transplantation, 2023)
The application of Vascularized composite allotransplantation (VCA) are increasing since the first successful hand transplantation in 1998. However, The abundance of muscle tissue makes VCA’s vulnerable to ischemia-reperfusion injury (IRI), which has detrimental effects on the outcome of the procedure, restricting allowable donor-to-recipient time and limiting its widespread use. The current clinical method is Static cold storage (SCS) and this allows only 6 hours before irreversible damage occurs upon reperfusion. In order to overcome this obstacle, the focus of research has been shifted towards the prospect of ex-vivo perfusion preservation which already has an established clinical role in solid organ transplants especially in the last decade. In this comprehensive qualitative review, we compile the literature on all VCA machine perfusion models and we aim to highlight the essentials of an ex vivo perfusion set-up, the different strategies, and their associated outcomes.